Further evidence for de novo variants in SYNCRIP as the cause of a neurodevelopmental disorder - Semino, Francesca; Schröter, Julian; Willemsen, Marjolein H.; Bast, Thomas; Biskup, Saskia; Beck-Woedl, Stefanie; Brennenstuhl, Heiko; Schaaf, Christian P.; Kölker, Stefan; Hoffmann, Georg F.; Haack, Tobias; Syrbe, Steffen (Human mutation, 2021)
SYNCRIP encodes for the Synaptotagmin-binding cytoplasmic RNA-interacting protein, involved in RNA-binding and regulation of multiple cellular pathways. It has been proposed as a candidate gene for neurodevelopmental disorders (NDDs) with autism spectrum disorder (ASD), intellectual disability (ID), and epilepsy. We ascertained genetic, clinical, and neuroradiological data of three additional individuals with novel de novo SYNCRIP variants. All individuals had ID. Autistic features were observed in two. One individual showed myoclonic-atonic epilepsy. Neuroradiological features comprised periventricular nodular heterotopia and widening of subarachnoid spaces. Two frameshift variants in the more severely affected individuals, likely result in haploinsufficiency. The third missense variant lies in the conserved RNA recognition motif (RRM) 2 domain likely affecting RNA-binding. Our findings support the importance of RRM domains for SYNCRIP functionality and suggest genotype-phenotype correlations. Our study provides further evidence for a SYNCRIP-associated NDD characterized by ID and ASD sporadically accompanied by malformations of cortical development and myoclonic-atonic epilepsy.